Retrograde Recanalization of the Celiac Artery via the Pancreaticoduodenal Arcade as a Safe and Valid Alternative to Antegrade Access. (August 2020) - Pedersoli, Federico; Zimmermann, Markus; Schulze-Hagen, Maximilian; Sieben, Paul; Barzakova, Emona; Goerg, Fabian; Keil, Sebastian; Gombert, Alexander; Kuhl, Christiane K.; Isfort, Peter; Bruners, Philipp
Purpose: The antegrade recanalization of an occlusion or high-grade stenosis of the celiac artery via the aorta often represents a technical challenge. A retrograde approach via the superior mesenteric artery and the pancreaticoduodenal arcade may be an alternative approach. Based on our experience, we assess the technical success and the short- and mid-term outcomes of this bailout procedure. Methods: We performed a retrospective analysis of all consecutive patients who underwent recanalization and stent implantation in the celiac artery between January 2010 and December 2018. Data on vascular access, the materials used including stents, as well as the length of the intervention, radiation exposure, and follow-up were assessed. Results: Recanalization in combination with stent implantation into the celiac artery was performed in 43 patients. In 39 (91%) of 43 patients, the recanalization was successful with an antegrade approach via the aorta, whereas in 4 (9%) of 43 patients the passage of the stenosis was possible only through a retrograde approach through the superior mesenteric artery and the pancreaticoduodenal arcade followed be advancement of the microwire through the celiac artery into the aorta. The tip of the microwire was captured in the aorta with a snare and pulled out in the femoral introducer sheath and used as a guide for the antegrade implantation of a balloon-expandable stent. Conclusions: The retrograde recanalization of the celiac artery via the pancreaticoduodenal arcade may be technically challenging yet represents a feasible alternative in case of a failed antegrade approach.